Zygmunt Bauman and the theory of culture - Brzeziński, Dariusz (McGill-Queen's University Press, 2022)
"One of the most influential intellectuals of the twentieth and twenty-first centuries, sociologist and philosopher Zygmunt Bauman (1925-2017) made reflection on culture a fundamental part of his academic work. Publishing a substantial number of papers on the topic, many of his concepts would go on to significantly influence the social sciences and humanities. Bauman began his theoretical studies on culture when working at the University of Warsaw, and continued them all his life. Inspired by the many intellectual currents he encountered over his more than six decades of work, Bauman wrote on culture in the contexts of such issues as Marxism and socialism, modernity and the Holocaust, postmodernity and liquid modernity, and the contemporary nostalgia. In Zygmunt Bauman and the Theory of Culture Dariusz Brzeziński uses the evolution of Bauman's theory of culture as a prism through which to offer a comparative analysis, putting Bauman's work in conversation with the writings of other contemporary intellectuals. In this first comprehensive and critical assessment of Bauman's life-long work on culture, Brzeziński includes Bauman's papers and books from the Polish-language period of his writing, as well as his works discovered only posthumously, presenting them to an international audience."--